ANALISIS NILAI NASIONALISME MENGGUNAKAN MEDIA POSTER PILAR KARAKTER PADA SISWA KELAS III SEKOLAH DASAR - Irawati, Yuni; Kartika Dewi, Galuh; Rahmawati, Ery (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low nationalism values of third-grade elementary school students, which are shown through dishonest behavior, lack of respect for teachers and friends, and lack of responsibility for school tasks and rules. This study aims to describe the values of nationalism which include aspects of honesty, respect, and responsibility through the use of Character Pillar Poster media in third-grade students of SDN Terik Krian Sidoarjo. The study used a descriptive quantitative approach with 19 third-grade students as research subjects. Data collection techniques were carried out through observation and Likert scale questionnaires compiled based on nationalism value indicators. Data were analyzed using descriptive statistics in the form of score calculations and percentages to determine the achievement category of each aspect. The results of the study show that the use of Character Pillar Poster media is able to help instill nationalism values in students. Aspects of honesty, respect, and responsibility are in the good to very good category. Based on the analysis of the three aspects of nationalism values, the results show figures of 88.15% for honesty, 89.21% for mutual respect, and 87.76% for responsibility. All three aspects fall into the "very good" category.Character Pillar Poster media functions as a visual reminder that helps students understand and apply positive behavior in everyday life in the school environment. Thus, Character Pillar Poster media can be used as an alternative learning media for Pancasila Education to support character building and strengthening nationalism values in elementary school students.